Retrieval of Airglow Emission Rates in Analytical Form for Limb‐Viewing Satellite Observations at Low Latitudes. Issue 10 (7th October 2021) - Tam, Sunny W. Y.; Chiang, Chih‐Yu; Huang, Ke‐Chen; Chang, Tzu‐Fang
Abstract: The observation strategy of the limb‐viewing Imager of Sprites and Upper Atmospheric Lightning (ISUAL) payload aboard the FORMOSAT‐2 spacecraft inspires our development of a method to retrieve the volume emission rates from an array of airglow radiance measurements. The retrieval can be performed simply by evaluation of an analytical formula. The method can be applied to radiation at any wavelength, and its utilities are demonstrated in a reconstructed observation event of the 630.0‐nm OI airglow based on model‐generated emission rates. The simulated observation shows that radiance measurements may underestimate the heights of airglow locations by as much as 20 km. But application of the method to retrieve the emission rate profiles can recover the airglow locations with good accuracy, on average missing the height of the peak emission rate by only 2 km or so, corresponding to only 1–2 grid points in the calculations. The retrieval of airglow locations remains quite accurate even when the effect of noise is incorporated into the array of simulated radiance. Accuracy of the retrieved emission rates improves with the range of the field of view in the vertical direction. The method is also able to resolve the interference between the OI and OH emissions in the radiance data, separating the sources of the two types of emissions at distinctly different altitudes in the retrieved emission rate profiles. Overall, consideration of the reasoning behind this retrieval method could be useful for designing future satellite missions that focus on airglow research. Key Points: Retrieval of airglow emission rates from radiance measurements simply by evaluation of an analytical formula Method with good accuracy in finding the locations of airglow based on the retrieved volume emission rates Reasoning behind the retrieval method could help the designs of future satellite missions that focus on airglow research